Arsenic Removal by Solar‐Driven Membrane Distillation: Modeling and Experimental Investigation with a New Flash Vaporization Module. (1st January 2013) - Pal, Parimal; Manna, Ajay Kumar; Linnanen, Lassi
Abstract : A modeling and simulation study was carried out on a new flux‐enhancing and solar‐driven membrane distillation module for removal of arsenic from contaminated groundwater. The developed new model was validated with rigorous experimental investigations using arsenic‐contaminated groundwater. By incorporating flash vaporization dynamics, the model turned out to be substantially different from the existing direct contact membrane distillation models and could successfully predict (with relative error of only 0.042 and a Willmott d‐index of 0.997) the performance of such an arsenic removal unit where the existing models exhibited wide variation with experimental findings in the new design. The module with greater than 99% arsenic removal efficiency and greater than 50 L/m 2 ·h flux could be implemented in arsenic‐affected villages in Southeast Asian countries with abundant solar energy, and thus could give relief to millions of affected people. These encouraging results will raise scale‐up confidence.